Designing of Flow Mortar Design Mix for Self Compacting Concrete (SCC) with FWC = 0.4 - Noor Adi Wibowo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Self Compacting Concrete (SCC) is an innovation to produce concrete that could flow independently without being compacted. One of the practical methods is by making the mortar mix design first. The purpose of this research was to find optimum value of the flow mortar which will be base in the design of self-compacting concrete; and to find the optimum ratio of the mortar’s absolute volume to the volume of coarse aggregate cavity. The mortar material used type I cement, silica fume content 10% of cement weight, ratio of cement and grade III cement was of 1:1.25; water-cement factor of 0.4; and superplasticizer content of 0.3%, 0.4%, 0.5%, and 0.6% of cement weight. In this design of self-compacting concrete, the ratio of mortar absolute volume to coarse aggregate cavity were of 1.4, 1.6, and 1.8 with size of coarse aggregate of 10-20 mm. This research showed the optimum content of superplasticizer on mortar was of 0.6% which resulted slump flow of 260 mm, and compressive strength of 57.44 MPa. The testing result of SCC showed optimum value on ratio of mortar absolute-volume to coarse aggregate cavity was of 1.8 resulted slump flow of 280 mm, and compressive strength of 65.76 MPa.